Enhanced IL-12 transgene expression improves oncolytic viroimmunotherapy - Kim, Yeaseul; Saini, Uksha; Kim, Doyeon; Hernandez-Aguirre, Ilse; Hedberg, Jack; Martin, Alexia; Mo, Xiaokui; Cripe, Timothy P.; Markert, James; Cassady, Kevin A.; Dhital, Ravi (Frontiers in Immunology, 2024)
Malignant peripheral nerve sheath tumors (MPNSTs) are aggressive sarcomas with unacceptably low cure rates occurring often in patients with neurofibromatosis 1 defects. To investigate oncolytic Herpes Simplex Virus (oHSV) as an immunotherapeutic approach, we compared viral replication, functional activity, and immune response between unarmed and interleukin 12 (IL-12)-armed oncolytic viruses in virus-permissive (B109) and -resistant (67C-4) murine MPNSTs. These studies also compared two attenuated IL-12-oHSVs with γ134.5 gene deletions (Δγ134.5) and the same transgene expression cassette. The primary difference in the IL-12-oHSVs was in their ability to counter the translational arrest response in infected cells. Unlike M002 (Δγ134.5, mIL-12), C002 (Δγ134.5, mIL-12, IRS1) expresses an HCMV IRS1 gene and evades dsRNA activated translational arrest in infected cells. Our results show that oHSV replication and gene expression results in vitro were not predictive of oHSV direct oncolytic activity in vivo. Tumors that supported viral replication in cell culture studies resisted viral replication by both oHSVs and restricted M002 transgene expression in vivo. Furthermore, two IL-12-oHSVs with equivalent transcriptional activity differed in IL-12 protein production in vivo, and the differences in IL-12 protein levels were reflected in immune infiltrate activity changes as well as tumor growth suppression differences between the IL-12-oHSVs. C002-treated tumors exhibited sustained IL-12 production with improved dendritic cells, monocyte-macrophage activity (MHCII, CD80/CD86 upregulation) and a polyfunctional Th1-cell response in the tumor infiltrates. These results suggest that transgene protein production differences between oHSVs in vivo, in addition to replication differences, can impact OV-therapeutic activity.